Le generazioni su YouTube Italia (Schermi. Storie e culture del cinema e dei media in Italia, 2020)
The essay deals with the generations on YouTube Italia, and particularly with the partition of the phenomenon, linked to the modes of representation (and, often, overexposure) of individual, domestic and microsocial experience: from toys unboxing to bereavement vlogs, passing through the practices of adolescents and young adults. The aim is to track the progress of some YouTube logics along this ideal generational line. Alongside some general phenomena - also present in Italian videos - the article highlights some specificities of YouTube Italia, presented through a selection of emblematic cases.
Keywords: YouTube; Intimacy; Generations; Italy